2015
DOI: 10.1097/aln.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Protective versus Conventional Ventilation for Surgery

Abstract: These data support the beneficial effects of ventilation with use of low VT in patients undergoing surgery. Further trials are necessary to define the role of intraoperative higher PEEP to prevent PPC during nonopen abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 286 publications
(109 citation statements)
references
References 38 publications
5
100
1
3
Order By: Relevance
“…One more recent randomized controlled trial, however, showed no difference in the incidence of pulmonary complication when two different levels of PEEP were compared during low tidal volume ventilation [50]. Interestingly in this context is that a recent individual patient meta-analysis of intraoperative ventilation settings suggests that benefit mainly comes from tidal volume reductions, and not increases in PEEP, in patients undergoing mechanical ventilation for general anesthesia for surgery [51]. …”
Section: Discussionmentioning
confidence: 99%
“…One more recent randomized controlled trial, however, showed no difference in the incidence of pulmonary complication when two different levels of PEEP were compared during low tidal volume ventilation [50]. Interestingly in this context is that a recent individual patient meta-analysis of intraoperative ventilation settings suggests that benefit mainly comes from tidal volume reductions, and not increases in PEEP, in patients undergoing mechanical ventilation for general anesthesia for surgery [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Although use of higher tidal volumes may be influenced by inaccuracies in calculating PBW, it is also likely that a belief may continue among anesthesiologists that lower tidal volumes are harmful 1416. However, high quality data exist to suggest the opposite 9444546474849…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…Regardless, the results contribute to a body of evidence that is still inconclusive regarding the benefit of higher PEEP in the intraoperative population. For example, an updated patient level meta-analysis after PROVHILO showed no difference in incidence of PPC between patients ventilated with less than 5 cm H 2 O and those with 5 cm H 2 O or higher PEEP 49. Drawing from this conclusion and incorporating the knowledge from the ARDS literature that high PEEP may benefit only patients with more severe disease, it may be reasonable to infer that higher PEEP is not necessary for most of the intraoperative population but can be considered for patients at very high risk for atelectasis or with concomitant lung injury 65.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
See 1 more Smart Citation
“…results Logistic regression analysis showed active smoking was associated with an increase in ARDS (OR 3.91; 95% CI 1.33 to 11.5) and dihydropyridine use (OR 5.34;95% CI 1.56 to 18.3). Hospital length of stay was longer for those who took dihydropyridines (median 29 days (IQR 17-42) vs 13 days (IQR 10-18), P=0.0007) or were diabetic (median 25 days (IQR 14-39) vs 13 (IQR [10][11][12][13][14][15][16][17][18][19], P=0.023) but not for current smokers (median in never/ex-smokers 13 (IQR 10-23) vs current smokers [15][16][17][18][19][20], P=0.73). conclusions Smoking cessation trials should be promoted.…”
mentioning
confidence: 99%